Perancangan Arsitektur Sistem Informasi Pengelolaan Data Feedback di Perusahaan Pertambangan Batubara menggunakan TOGAF ADM - Aisha Edna Alicia Sanyoto; Aditya Rachmadi; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT Kaltim Prima Coal is the largest coal mining company in the world. PT Kaltim Prima Coal carries out the process of extracting coal to manage it until it is ready to be distributed to customers. One of the departments at PT Kaltim Prima Coal is the CPPM department where this department focuses on repairing and maintaining coal processing machines. The CPPM Department is required to carry out follow-up actions for machine damage quickly, effectively and efficiently. One of the business processes related to these demands is the business process for managing data feedback in the CPPM Department. Currently, the process of managing feedback data is still carried out using a manual system and simple applications such as Microsoft Excel and Whatsapp, so an effective, efficient and integrated IS/IT is needed. To overcome the problems that arise from the manual data feedback management process, it is necessary to design an enterprise architecture in the CPPM Department to align business strategy with IS/IT strategy and requires careful planning to plan and manage IS/IT. This study uses the TOGAF (The Open Group Architecture Framework) enterprise architecture framework design with the ADM (Architecture Development Method) method. This research is limited to phase C Information System Architecture. The design produces a blueprint of the proposed business architecture and information system architecture for managing data feedback in CPPM Department of PT Kaltim Prima Coal.Based on the evaluation results it is known that the business architecture model has 100% validity based on syntactic, semantic, and pragmatic quality and the degree of completeness between the quality attributes of the information system design that is built reaches 66.67%